Improvement of Serum Biochemical Parameters and Hematological Indices Through α-Tocopherol Administration in Dietary Oxidized Olive Oil Induced Toxicity in Rats - Zeb, Alam; Khan, Ayaz Ali (Frontiers in Nutrition, 2019)
Dietary oxidized olive oil, alone or in combination with different doses of α-tocopherol, were given to Swiss albino rats for 30 days; in order to determine its role in oxidative stress and fatty liver, induced by the oxidized olive oils. Serum biochemical parameters and haematological indices of blood were analyzed. The liver was analyzed for histopathological changes, lipid peroxidation, and polar triacylglycerols composition. Results revealed that there was a significant decline in the serum total cholesterol, triglycerides, LDL, glucose and ALT; while significant increase occurred in the serum HDL levels by the supplementation of α-tocopherol in male and female rats. Haematological parameters were almost in normal reference range in groups that were fed with α-tocopherol, alone or in combination with oxidized oil, while significantly altered by the oxidized olive oil. There were acute hepatitis and necrosis in the liver with no fatty changes after feeding with oxidized olive oil, along with varying doses of α-tocopherol. Higher amounts of polar compounds were present in female rats (15.2-93.1 µg/g) compared to male (12.2-82.3 %) that corresponds to the supplementation of α-tocopherol in combination with oxidized oil. Lipid oxidation in liver was minimized by tocopherol, while an increase occurred in the accumulation of oxidized lipids in the liver. These findings revealed that tocopherol was beneficial against the oxidized oil induced biochemical and haematological changes and lipid peroxidation, but caused fatty accumulation in the liver. Therefore, the role of tocopherol in patients with fatty liver may be considered, as tocopherol may increase its chances.